Sexual violence against intimate partners in Cape Town: prevalence and risk factors reported by men - Abrahams Naeemah; Jewkes Rachel; Hoffman Margaret; Laubsher Ria (The World Health Organization, 2004)
OBJECTIVE: To describe the prevalence of and risk factors for the perpetration of sexual violence by men against female intimate partners. METHODS: A cross-sectional study was conducted on 1368 randomly selected men working in three Cape Town municipalities. The men were interviewed with the aid of a questionnaire on current sexual partners in the preceding 10 years, personal and relationship characteristics and the use of violence against their partners. RESULTS: The perpetration of sexual violence against intimate partners in the past 10 years was reported by 15.3% of the men. After adjustment for sociodemographic circumstances, the factors associated with such violence were involvement in physical conflict outside the home, problematic alcohol use, having more than one current partner and abusing partners verbally. While having frequent conflict with partners was important for the risk of sexual violence, only two types of conflict sources were significantly associated with this risk, namely conflict over sexual refusal and conflict when men perceived their authority to be undermined. CONCLUSION: Sexual violence in intimate relations was common. The risk of being sexually violent was associated with the use of violence to solve problems in other settings, having more than one current partner, alcohol abuse and verbally abusing a partner. It was also associated with particular types of conflict stemming from ideas of male sexual entitlement and dominance. Prevention programmes that focus on gender relations and non-violent conflict resolution for men and youths may be useful in combating such sexual violence.